Trajectories of Pain Intensity Over 1 Year in Adults With Disabling Subacute or Chronic Neck Pain. Issue 8 (August 2019) - Pico-Espinosa, Oscar J.; Côté, Pierre; Hogg-Johnson, Sheilah; Jensen, Irene; Axén, Iben; Holm, Lena W.; Skillgate, Eva
Abstract : Objectives: The objectives of this study were to describe the 1-year trajectories of disabling subacute or persistent neck pain and to investigate whether baseline age, sex, pain characteristics, and depressive symptoms are associated with such trajectories. Study Design and Setting: Participants (n=617) included in a randomized controlled trial provided weekly pain intensity ratings by responding to text messages over 1 year. We used latent class mixed model analyses to identify clusters of individual trajectories. Thereafter, we used logistic regression to determine the association between baseline age, sex, pain characteristics, depressive symptoms and treatment, and trajectories of neck pain. Results: Six different clusters of trajectories were identified. Most participants (73%) followed a trajectory of decreasing pain throughout follow-up. The remaining experienced unfavorable trajectories: persistent pain of high intensity (22%) and slightly (3%) or highly (2%) fluctuating levels of pain reaching high levels of pain intensity. Pain intensity at baseline: odds ratio (OR): 3.76 (95% confidence interval [CI]: 2.49-5.68), depressive symptoms: OR: 3.46 (95% CI: 2.01-5.95), younger age: OR: 2.29 (95% CI: 1.48-3.54), female sex: OR: 1.51 (95% CI: 1.01-2.26), and sudden onset of pain: OR: 1.74 (95% CI: 1.13-2.69) were associated with unfavorable trajectories. Conclusions: Most individuals with disabling subacute or chronic neck pain show improvement in pain intensity over a year. However, a quarter present unfavorable trajectories. High pain intensity at baseline, depressive symptoms, younger age, female sex, and sudden onset of pain are factors associated with unfavorable trajectories. Abstract : Supplemental Digital Content is available in the text.